2011
DOI: 10.1007/s00217-011-1613-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of winemaking technologies on phenolic composition of Italian red wines

Abstract: The aim of this study was to assess the influence of different winemaking technologies on the chemical characteristics and, in particular, on the phenolic fraction of Aglianico, Montepulciano, Nero di Troia and Sangiovese wines produced in Apulia, Southern Italy. Four different winemaking technologies were compared: control (traditional, 5 days of maceration at 25°C with three daily punching-down), prolonged maceration (10 days), addition of ellagic tannins, and cryomaceration (24 h at 5°C using dry ice), with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 29 publications
1
29
1
1
Order By: Relevance
“…The cold prefermentative process did not increase the anthocyanin levels; control wines had higher contents of these pigments in every vintage (Fig. 4) that agrees to the results of many papers Pérez-Lamela et al 2007;Puertas et al 2008;Gil-Muñoz et al 2009;Gambacorta et al 2011). However, several works showed an increase in the anthocyanin contents of wines produced by pre-fermentative maceration at low temperature (Table 1), affect strongly the effect of the pre-fermentative skin contact on the release of these compounds.…”
Section: Anthocyanin Composition Of Winessupporting
confidence: 89%
See 3 more Smart Citations
“…The cold prefermentative process did not increase the anthocyanin levels; control wines had higher contents of these pigments in every vintage (Fig. 4) that agrees to the results of many papers Pérez-Lamela et al 2007;Puertas et al 2008;Gil-Muñoz et al 2009;Gambacorta et al 2011). However, several works showed an increase in the anthocyanin contents of wines produced by pre-fermentative maceration at low temperature (Table 1), affect strongly the effect of the pre-fermentative skin contact on the release of these compounds.…”
Section: Anthocyanin Composition Of Winessupporting
confidence: 89%
“…Nevertheless, the effect of technology on the anthocyanin composition of wines needs to be further investigated, since it seems to be linked to the intrinsic characteristics of grapes in terms of ripening and richness in phenols (Gambacorta et al 2011). …”
Section: Anthocyanin Profile Of Winesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors (ROMERO-CASCALES et al, 2005;MORENO-ARIBAS et al, 2008) found that the fi ngerprint of grapes was different from the one of the elaborated wines, and infl uenced by the technology applied in their winemaking. On the other hand, others (GAMBACORTA et al, 2011;PUÉRTOLAS et al, 2011) reported that extraction of phenolics from grape skins to wine was mostly depending on the grape variety rather than on the applied winemaking technology. Nevertheless, if some correlation between the grape and wine anthocyanin patterns could be confi rmed, it may be used for authentication purposes and controlling the origin of the wine.…”
Section: Anthocyanin Pattern Of Grapes Vs Corresponding Winesmentioning
confidence: 99%